Kebutuhan Air Bersih di Kota Bontang - Sumendar, Rian; Yasin, Azalia Fajri (Jurnal Teknologi Lingkungan Lahan Basah, 2023)
The development of the National Capital City (IKN) is expected to have a huge impact on East Kalimantan Province in terms of development and economic activity as well as population growth. Bontang City is one of the IKN Supporting Cities which is expected to become a new economic growth area. Currently, Bontang City has a population of 186,137 people recorded through the e-INFODUK service in East Kalimantan Province, population growth will increase with the presence of IKN which will move completely in 2030. Using the exponential projection method, it is estimated that the population of Bontang City is 192,579 people. with a clean water requirement of 267 l/sec, and the availability of clean water for Bontang City in 2030 of 316.56 l/sec. Thus the availability of clean water in Bontang City needs to be a concern in increasing the capacity of clean water